Fear of Covid-19 and health-related outcomes: results from two Brazilian population-based studies - Meller, Fernanda Oliveira; Schäfer, Antônio Augusto; Quadra, Micaela Rabelo; Demenech, Lauro Miranda; Paludo, Simone dos Santos; da Silva, Priscila Arruda; Neiva-Silva, Lucas; Dumith, Samuel C. (Psychiatry research, 2022)
•There was a linear trend between fear of Covid-19 and health-related outcomes.•Higher fear of Covid-19 was related with worse sleep quality and worse health perception.•Individuals with depressive symptoms and suicidal ideation presented higher fear.•Higher fear was associated with sadness and higher stress.•Living alone, being richer and have tested positive was related with lower fear. Fear is a reaction that can influence multiple aspects of health and life. During the Covid-19 pandemic, there have been serious pathophysiological, social, behavioral and mental consequences that can be related to fear. This study aimed to assess the fear of Covid-19 and its association with sociodemographic, behavioral and health variables. Data were gathered from two cross-sectional population-based studies conducted in 2020 with adults from two cities from Southern Brazil. The Fear of Covid-19 scale was used to evaluate fear of Covid. Exposure variables were socioeconomic, demographic, health and pandemic-related factors. Adjusted Poisson regression was performed to assess the association between fear of Covid-19 and the exposure variables. A total of 2,152 subjects were assessed. Higher fear of Covid-19 was found among women and in individuals with symptoms of Covid-19. Living alone, being richer, and testing positive for Covid-19 were associated with lower prevalence of fear. Higher prevalence of fear of Covid-19 was related to worse sleep quality, worse health perception, sadness, higher stress, depressive symptoms, and suicidal ideation. There was a linear association between fear of Covid-19 and health outcomes. The results provide evidence that fear of Covid-19 seems to be associated with socioeconomic, demographic, health and pandemic-related factors.